Influential Factors for Effective Materials Management in Construction Projects - Mat Jusoh, Zairra; Kasim, Narimah; Umar Ibrahim, Magaji; Sarpin, Norliana; Mohd Noh, Hamidun; Zainal, Rozlin (International Journal of Sustainable Construction Engineering and Technology, 2018)
Construction projects are plagued with the issue of poor project performance such as low productivity, wastage, time overrun, compromised quality and cost overrun. Research literature reveals that this issue occurs partly due to ineffective materials management. Nonetheless, the effective management of materials seems like a viable solution to enhance the performance of any construction projects. Despite its importance, not much literature has explored the influential factors for effective management of materials. Since the identification of factors is an essential step to recommend any improvement efforts, thus, this paper examines the influential factors for effective materials management. A questionnaire survey was conducted with practitioners from contractor organisations and 111 valid responses were obtained. Data was analysed using exploratory factor analysis via the IBM SPSS version 21 software. Results indicate that only 50 influential factors were relevant in Malaysian construction project and these were categorised into 8 specific components namely: management, purchasing, expediting, transportation, site storage and condition, supplier, contractual and governmental interference. Summarily, findings reported in this paper constitute part of a questionnaire development process for a research project undertaken to develop an effective materials management model for better projects performance. Thus, the outcome of this study may assist practitioners in decision making process by understanding the identified influential factors that contribute to effective materials management.